Prototypical values self-report in the avoidant personality disorder - Alvarez Ramirez, Leonardo Yovany (2018)
This study conducted convergent validation on participant’s identification with the prototypical values of histrionic personality disorder repertoire, an important part of acceptance and commitment psychotherapy (ACT). The Multiaxial Inventory of Personality (MCMI – III) was administered to two mixed groups of participants (cases versus controls). Participants were also interviewed using the SCID- II,and a structured interview The content analysis of the structured interviews showed that participants with the disorder had the highest mean in the “A-R-VP self-report identification” at all the 12 values examined on a 0 to 5 point scale, with scores closer to 5. Meanwhile, those without the disorder had scores of identification between 0 and 1. The results of the Student t test confirmed the findings. People with histrionic personality disorder identify themselves with a repertoire of twelve characteristic values of this disorder.